Importance of irrigated agriculture to the Ethiopian economy: capturing the direct net benefits of irrigation - Hagos, Fitsum; Makombe, Godswill; Namara, Regassa E.; Awulachew, Seleshi Bekele (2008)
Irrigation development is seen as one of the means to reduce poverty and promote economic growth. While a lot of effort is exerted towards irrigation development, little attempt is done to quantify the contribution of irrigation to national income in Ethiopia. This study is an attempt to quantify the actual and expected contribution of irrigation to the Ethiopian national economy for 2005/06 cropping season and 2009/10 using adjusted net gross margin analysis. Our results show that irrigation in the study sites generates an average income of about USD 323/ ha. This compares to the calculated gross margin for rainfed which is USD 147/ha. This indicates that after accounting for annual investment replacement cost net gross margin from irrigation is more than twice higher than gross margin from rainfed agriculture. On the contribution of irrigation to national economy, in 2005/06 smallholder irrigated agriculture contributed about 262.3 million USD. This accounts for about 4.46 percent of the agricultural GDP in 2005/2006 and 1.97 percent of the total overall GDP. The total income earned from large scale schemes is estimated to be about 74.0 million USD. This accounts for about 1.26 percent of the agricultural and 0.5 percent of the total GDP respectively. Overall, the contribution of irrigation to agricultural and total national GDP was about 5.7 and 2.5 percent during the 2005/06 cropping season. As a result of expansion, by the year 2009/2010 the expected contribution of smallholder managed irrigation to national economy, assuming that exiting cropping pattern, and the average gross margin values for different crop categories are still valid, is expected to increase from USD 262.3 million in 2005/2006 to about USD 414.2 million in 2009/2010, which accounts to about 5.5 percent of the agricultural GDP and 2.3 of the overall GDP for the same year. On the other hand, the contribution coming from the large scale sugar growing estates in 2009/2010 is estimated to be USD 217.5 million which amounts to 2.9 and 1.2 percent of the agricultural and overall GDP respectively. Similarly the contribution coming from large scale commercial farms growing crops other than sugar cane is expected to increase to USD 35.8 million in 2009/2010 which accounts to 0.4 and 0.2 percent of the agricultural and overall GDP respectively. This implies that large scale commercial farms will contribute about 3.3 and 1.4 of the agricultural and overall GDP respectively. In summary, our results indicate that under conservative estimates the future contribution of irrigation to agricultural and overall GDP will be about 9 and 3.7 percent respectively. When some of the assumptions related to cropping pattern, input and output prices, 128 and efficiency levels are relaxed, the contribution of smallholder managed irrigation to agricultural and overall GDP will vary between 4 to 6 and 1.8 to 1.9 percent respectively. Similarly, the contribution from large scale irrigation to agricultural and overall GDP will be in the range of 3 to 6 and 1.2 to 2.5 percent respectively. Overall, the future contribution of irrigation to agricultural GDP will be in the range of 7 to 12 percent while the contribution to overall GDP will be in the range of about 4 percent. To enhance the contribution of irrigation to national economy, besides increasing the presence of physical water infrastructure, however, there is a need to: i) improve provision of agricultural inputs, ii) promote high value crops through the extension system, iii) create good market conditions, and iv) increase the efficiency of small and large schemes.